Gelasian stage and expected stratigraphical units having similar ages in Viet Nam - Dy, Nguyen Dich; Luong, Le Duc; Tao, Nguyen Van; Thanh Ha, Trinh Thi; Anh, Nguyen Thanh Tuan; Cuong, Nguyen Manh (Vietnam Journal of Earth Sciences, 2015)
During recent years (2009-2013), International Commission on Stratigraphy (ICS) has published International Chronostratigraphic Charts with the increasing trend on the quantity of Quaternary. The lower part of Quaternary has supplemented the stage of Gelasian leading to the increasing time of Quaternary from 1,6 - 1,8 million years to 2,588 million years. In Viet Nam, geologists are currently using the time from 1,6 - 1,8 million years to present for Quaternary.In order to integrate into the international geological community, Quaternary in Viet Nam needed to be studied and added more stratigraphical units with the ages of Pliocene to fit the time of 2,588 million years. In this paper, we propose two related scientific idioms:- Exclude the upper Pleistocen of Ha Noi formation of Ha Noi depression, Ba Mieu formation  (Nam Can) of Cuu Long river plain, Thach Han formation (Vo Dac) of Central of Viet Nam.In addition, detailed studies on paleontology, sedimentary, paleomagnetic, absolute age, stratigraphical events…needed to be continuously invested for implementation in the future.ReferencesIUGS ratified ICS Recommendation on redefinition of Pleistocene and formal definition of base of Quaternary, June 30th 2009. (Source: www.stratigraphy.org). Tống Dzuy Thanh và Vũ Khúc (chủ biên), 2005. Các phân vị địa tầng Việt Nam. Nhà xuất bản Đại học Quốc gia Hà Nội, 553tr. Nguyễn Địch Dỹ, 1987. Địa tầng và cổ địa lý trầm tích Kainozoi Việt Nam. Luận án Tiến sĩ Khoa học, tiếng Nga, 380tr.